Quality and inequality in urban and regional systems - Karima Kourtit; Peter Nijkamp; Roger Stough (REGION, 2018)
In the aftermath of both ongoing globalisation (with both widening and deepening effects on countries, regions and cities) and structural changes resulting from the 2008 economic recession, regions and cities in our world are confronted with a different arena of players, performances and institutions. The challenges are formidable and numerous. Many regions and cities seem to resort to their indigenous strength, without much regard to other players in the field. This has enormous consequences for the competitive behaviour and profile of regional and urban actors but has at the same time deep impacts on the distribution of wealth, income and employment over and within countries, regions and cities. There is indeed much evidence that disparities among regions and in cities are increasing in this new force field. This special issue of REGION makes a solid scientific attempt (i) to map out the spatial consequences of recent transitions in growth trajectories of countries or regions, and (ii) to trace policy strategies and design effective policy information, to cope adequately with these new challenges. The present special issue does so by highlighting the new force field of regional and urban dynamics from three angles in the context of spatial quality and inequality. These will be briefly sketched below.
Keywords: 330